Brief considerations on Hogan's legacy: his contributions to socio-environmental studies - Seixas, Sonia Regina da Cal (Universidade Estadual de Campinas, 2021)
The main goal of this article is to reflect on the contribution of Daniel Hogan's pioneering work to the consolidation of the socio-environmental studies at the State University of Campinas (UNICAMP). Due to his vast intellectual production, it would be impossible to fully address this topic in this space, thus, we chose to highlight a personal selection of printed works and projects considered seminal and representative for this approach. It is noteworthy that the task of making this choice was not easy due to the magnitude and scope of the work left by him, with his unique performance on various fronts and approaches to the socio-environmental theme in its different dimensions. However, our choice is centered on the constitution of the socio-environmental dimension from the Social Sciences, for which he has offered important theoretical contributions in recent decades, serving as the basis for numerous works, research projects, training of academics and the consolidation of a privileged space of action that remains until today as a reference of this tradition, which is the Center for Environmental Studies and Research – NEPAM – at UNICAMP, of which he was one of the founders and coordinator in the period from 1991 to 1997.